Bank Liability to Customers in Cases of Skimming and Account Break-Ins Civil Law Perspective - Nurul Rahmadini Manggasali; M. Bruri Wutwensa; Y. Yakoba Hattu (Sidyanusa, 2026)
This study aims to analyze the legal liability of banks toward customers who suffer losses caused by skimming and account breaching, and to axime the extent to wich Indonesia’s positive law provides legal protection for customers. This research uses a normative legal method with statutory and conceptual approaches through library research. Data were collected from laws and regulations, legal literature, journals, and relevant court decisions. The result show that skimming and account breaching are cybercrimes that directly cause finansial losses to customers. Bank liability can be claimed through breach of contract (wanprestasi) and unlawful act (perbuatan melawan hukum) as regulated in the Indonesia Civil Code, as well as under the Banking Law and the Consumer Protection Law. Meanwhile, the ITE Law provedis criminal sanstions for perpetrators of cybercrime. However, in practice, legal protection for customers remains ineffective. The Selayar District Court Decision No.30/Pid.Sus/2019/PN.Slr shows that although perpetrators may be punished, customer compensation must still be pursued through civil proceedings or consumer protection mechanisms. This indicates a gap between legal norms and their implementation in practice.